1990
DOI: 10.1182/blood.v75.8.1733.bloodjournal7581733
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human adenosine deaminase in mice after transplantation of genetically-modified bone marrow

Abstract: A high titer retroviral vector was used to transfer a human adenosine deaminase (h-ADA) cDNA into murine bone marrow cells in vitro. The h- ADA cDNA was linked to the retroviral promoter, and the vector also contained a neomycin phosphotransferase gene as a selectable marker. Infected marrow was transplanted into syngeneic W/Wv recipients, and h- ADA expression was monitored for 5.5 months. Several weeks after transplantation, h-ADA was detected in the erythrocytes of all nine recipients, eight of which expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…As a control that the labeling of host fibers with/%gal arose from the fusion of implanted myoblasts and not from the direct transfer of genetic material (Kaleko et al, 1990), we performed syngeneic transplants of fibroblast enriched cultures that were/~-gal labeled by retroviral transduction. Muscles were examined two days to six weeks after transplantation of 1@ -4 x 105 fibroblasts.…”
Section: Hybrid Myofibers Formed By Primary Myoblast Transplantationmentioning
confidence: 99%
“…As a control that the labeling of host fibers with/%gal arose from the fusion of implanted myoblasts and not from the direct transfer of genetic material (Kaleko et al, 1990), we performed syngeneic transplants of fibroblast enriched cultures that were/~-gal labeled by retroviral transduction. Muscles were examined two days to six weeks after transplantation of 1@ -4 x 105 fibroblasts.…”
Section: Hybrid Myofibers Formed By Primary Myoblast Transplantationmentioning
confidence: 99%
“…An intensively studied model system for gene therapy utilizes the hematopoietic reconstitution of irradiated mice with genetically modified syngenic bone marrow (1)(2)(3)(4)(5). For this approach to be successful very efficient gene transfer into bone marrow stem cells must occur.…”
Section: Introductionmentioning
confidence: 99%
“…The freedom to manipulate PBS and primer sequences may address two critical points in relation to the advancement of retroviral gene transfer technology and its clinical usage. Firstly, a number of current studies have shown the wt PBS of MLV proviruses to be involved in transcriptional down-regulation of vectors in important target cells (4,7,16,24). Secondly, the risk for generation of replication-competent retroviruses has traditionally been reduced by manipulation of the viral packaging construct, by partition of the gag and pol genes and the env gene, and by the use of heterologous promoters and termination signals (21).…”
Section: Discussionmentioning
confidence: 99%